Espalhamento quântico unidimensional via mecânica quântica supersimétrica - Soares, Camila Correia (2017)
In this work, we study the formalism of the supersimmetric quantum mechanics (SUSY QM) starting with hamiltonian fatorization method of the bosonic harmonic oscillator (BHO) by means of ladders operators and we extended to hamiltonian of oscillators in general, inclusive of the fermionic harmonic oscillator (FHO), with their respective properties. We show that the SUSY QM for bound states, connect hamiltonians, potentials, and eigenvalues energy of different systems which are called supersymmetric partners. In the case scattering states, we notice that SUSY QM applies only in shape invariant potentials (SIPs). Despite this restriction, the SIPs are commonly used in literature by its wide applicability as in particles physics as in condensed matter. Therefore, we study the scattering states to the problem of massive relativistic fermions under the influence of modified Pöschl-Teller potential (PT), which is shape invariant. We calculate the transmission (T) and reflection (R) coefficients, just knowing the superpotential, which was carried out in a simple and elegant form. Thus, the study of the quantum scattering via SUSY QM becomes a powerful tool in the calculations of T and R.